The Effect of Company Size and Audit Fee on Audit Quality - Shaqilah, Diva Atari; Rusliyawati, Rusliyawati; Prihatini, Dwi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
There are several factors that can influence audit quality, including company size and audit fees. The aim of this research is to determine the factors related to audit quality in companies on the Indonesia Stock Exchange. The population data used in this research are companies in the property and real estate sector in the 2020-2023 period. This research is quantitative research. The data source used is secondary data in the form of company annual financial reports for the period 2020 to 2023. Sampling was carried out using a purposive sampling method and the data obtained was 10 companies as a sample with 40 observational data. The analytical method used in this research is multiple linear regression analysis. The results of this research show that the influence of company size has a positive effect on audit quality. Likewise, audit fees have a positive effect on audit quality, because the higher the audit provided by the company, the higher the auditor's performance.